2013
DOI: 10.3945/ajcn.112.045468
|View full text |Cite
|
Sign up to set email alerts
|

trans-Palmitoleic acid, other dairy fat biomarkers, and incident diabetes: the Multi-Ethnic Study of Atherosclerosis (MESA)

Abstract: Circulating trans-palmitoleate is associated with higher LDL cholesterol but also with lower triglycerides, fasting insulin, blood pressure, and incident diabetes in a multiethnic US cohort. Our findings support the need for further experimental and dietary intervention studies that target circulating trans-palmitoleate. The MESA trial was registered at clinicaltrials.gov as NCT00005487.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
191
3
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(213 citation statements)
references
References 29 publications
16
191
3
3
Order By: Relevance
“…When dyslipidemic subjects received capsules with 220.5 mg cis-palmitoleate for 30 d, there were significant reductions in C-reactive protein, TGs, and LDL cholesterol and a significant increase in HDL cholesterol (79). Also, the consumption of trans-palmitoleate from dairy was associated with lower amounts of inflammation, but mixed relations with serum lipids (19,33). In various studies (42,43,92), but not all studies (93), the consumption of macadamia nuts (which contain high cis-palmitoleate concentrations) was related to favorable serum lipid profiles.…”
Section: Cardiovascular Diseasementioning
confidence: 94%
See 1 more Smart Citation
“…When dyslipidemic subjects received capsules with 220.5 mg cis-palmitoleate for 30 d, there were significant reductions in C-reactive protein, TGs, and LDL cholesterol and a significant increase in HDL cholesterol (79). Also, the consumption of trans-palmitoleate from dairy was associated with lower amounts of inflammation, but mixed relations with serum lipids (19,33). In various studies (42,43,92), but not all studies (93), the consumption of macadamia nuts (which contain high cis-palmitoleate concentrations) was related to favorable serum lipid profiles.…”
Section: Cardiovascular Diseasementioning
confidence: 94%
“…In animal models, cis-palmitoleate decreased the expression of proinflammatory markers and adipokines, which are related to the establishment of metabolic abnormalities (16)(17)(18). Trans-palmitoleate (1) is found in dairy products and partially hydrogenated oils and may be associated with favorable metabolic profiles and decreased incident diabetes (19). Typically, trans FAs, which are produced for commercial cooking and frying, are related to a higher risk of endothelial dysfunction and coronary heart disease (20).…”
Section: Introductionmentioning
confidence: 99%
“…However, no association was shown between circulating trans palmitoleate and risk of ischemic heart disease (38) or stroke (8). For other health outcomes such as diabetes, trans palmitoleic acid was associated with a lower fasting insulin concentration and incident diabetes in a multiethnic US cohort (40). Furthermore, circulating concentrations of the 2 odd-chain FAs pentadecanoic acid and heptadecanoic acid have reasonable correlations with dairy fat intake and, thus, may be considered as weak biomarkers of dairy fat (8,38).…”
Section: Tablementioning
confidence: 99%
“…with two earlier studies that reported inverse associations between plasma trans-palmitoleic acid concentration and incident T2DM (44,45) . It remains unclear, however, whether trans-palmitoleic acid has a specific metabolic function, or whether it is simply a marker of dairy food intake.…”
Section: Nutrition Research Reviewsmentioning
confidence: 99%
“…A growing body of evidence suggests that milk and dairy product consumption is associated with a reduced risk of T2DM, possibly due to the beneficial effects of dairy products on obesity and the MetS, two important risk factors for T2DM, as well as the beneficial role of certain dairy components such as protein, Ca, vitamin D, dairy fat and specifically trans-palmitoleic acid (44,45) .…”
Section: Type 2 Diabetes Mellitusmentioning
confidence: 99%